2018
DOI: 10.3892/etm.2018.6957
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Qishen Yiqi dropping pills on the myocardium of rats with chronic heart failure

Abstract: Protective effect of Qishen Yiqi dropping pills on the myocardium of rats with chronic heart failure (CHF) was investigated. Sixty rats were divided into the sham operation (n=20), the model (n=20) and the Qishen Yiqi dropping pill treatment group (n=20) using the random table method. The treatment group received administration of Qishen Yiqi dropping pills. The model and the sham operation group were given the same amount of normal saline. Within 24 h after the last administration, the rats were sacrificed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Moreover, administration of QSYQ (T101) at higher dose of 465 mg/kg could significantly lower the blood pressure and improve the ventricular remodeling, collagen deposition and fibrosis in SHR-induced myocardial damaged model, namely pre-HF model. Above-mentioned results were in accordance with previous reports in animal models and clinical trials ( Lu et al, 2019 ; Lin et al, 2020 ; Guan et al, 2021 ). Moreover, QSYQ (T101) demonstrated regulation to the abnormality of serum and myocardial tissue metabolic profiles through several metabolomics pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, administration of QSYQ (T101) at higher dose of 465 mg/kg could significantly lower the blood pressure and improve the ventricular remodeling, collagen deposition and fibrosis in SHR-induced myocardial damaged model, namely pre-HF model. Above-mentioned results were in accordance with previous reports in animal models and clinical trials ( Lu et al, 2019 ; Lin et al, 2020 ; Guan et al, 2021 ). Moreover, QSYQ (T101) demonstrated regulation to the abnormality of serum and myocardial tissue metabolic profiles through several metabolomics pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Modern pharmacological research and clinical studies have demonstrated its effectiveness in the treatment of HF. Recent studies verified that QSYQ (T101) enhanced the degree of myocardial fibrosis by inhibiting the TGF-β1/Smads pathway and exerted an obvious myocardial protective effect on CHF rats (Lu et al, 2019). Chang et al showed that QSYQ (T101) has the inhibitory effects on ventricular remodeling, cardiac ischemia-reperfusion injury (Chang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of high-fat diet-induced heart failure with preserved ejection fraction (HFpEF), it was observed that QSYQ significantly improved cardiac function and myocardial remodeling in mice, possibly through the inhibition of microvascular endothelial inflammation and activation of the NO-cGMP-PKG pathway (46). In addition, it was also reported that, in coronary artery ligation-induced ischemic CHF rats, QSYQ intervention reduced myocardial infarct size and apoptosis and improved myocardial fibrosis (47). Interestingly, it was found that QSYQ also prevented doxorubicin-induced cardiotoxicity in mice, which may be closely related to enhanced cardiac angiogenesis (48).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…For instance, it did not deal with clinical multiple confounding factors; All-cause death and readmission rates, which reflect long-term prognosis, are not included in efficacy evaluation; The latest high-quality clinical study was not included. [ 8 , 9 ] Recently, the randomized controlled trial (RCT) of QSYQ treating HF involving the largest sample of 640 patients in 24 centers around the world was published. The study adds composite clinical outcomes (including all-cause mortality within 12 months, emergency treatment/ readmission owing to heart failure, cardiogenic shock, etc) as evaluation indicators for the first time.…”
Section: Introductionmentioning
confidence: 99%